2013
DOI: 10.1186/1477-7525-11-133
|View full text |Cite
|
Sign up to set email alerts
|

Development and calibration of an item bank for the assessment of activities of daily living in cardiovascular patients using Rasch analysis

Abstract: BackgroundTo develop and calibrate the activities of daily living item bank (ADLib-cardio) as a prerequisite for a Computer-adaptive test (CAT) for the assessment of ADL in patients with cardiovascular diseases (CVD).MethodsAfter pre-testing for relevance and comprehension a pool of 181 ADL items were answered on a five-point Likert scale by 720 CVD patients, who were recruited in fourteen German cardiac rehabilitation centers. To verify that the relationship between the items is due to one factor, a confirmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…52,53 Moreover, AIB-ortho builds a further puzzle for a comprehensive psychodiagnostics in orthopedic and cardiovascular patients using RehaCAT with its already established IRT and CAT dimensions depression, activity in daily living and work capacity as well as the parallel to this study developed item bank on patients’ treatment motivation. 19,27,45,47,4954,55…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…52,53 Moreover, AIB-ortho builds a further puzzle for a comprehensive psychodiagnostics in orthopedic and cardiovascular patients using RehaCAT with its already established IRT and CAT dimensions depression, activity in daily living and work capacity as well as the parallel to this study developed item bank on patients’ treatment motivation. 19,27,45,47,4954,55…”
Section: Discussionmentioning
confidence: 99%
“…An item bank is considered unidimensional if the 95% confidence interval of the number of significant tests overlaps 5%. 19,37,46,47…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of the project 'Development and validation of a computer-adaptive test for cardiac patients undergoing rehabilitation: RehaCAT-Cardio'. [22][23][24][25]…”
Section: Introductionmentioning
confidence: 99%
“…Comparing computer based assessment and paper-pencil methods Eisen et al (2004) found high correlations between these methods, indicating validity of computerized testing [24]. A computer based version of the WCIB-Cardio-SF would furthermore provide the possibility to integrate the WCIB-Cardio-SF in a battery of computer (adaptive) instruments such as the RehaCATCardio [25][26][27].…”
Section: Ijomeh 2013;26(5) 748mentioning
confidence: 99%